A revised intracarotid etomidate memory (Wada) procedure. (1st June 2012) - Andelman, F.; Kipervasser, S.; Maimon, S.; Fried, I.; Parmet, Y.; Neufeld, M. Y.
<x xml:space="preserve">Abstract</x> Objectives To evaluate unilateral memory function by the means of a modified Montreal etomidate speech and memory procedure (e‐SAM) in epilepsy patients who were candidates for standard anterior temporal lobectomy involving resection of mesial temporal lobe structures. Materials and methods After the first three patients experienced significant side effects with the e‐SAM procedure, we modified the procedure to a single bolus injection. The neuropsychological data of all 21 patients who underwent unilateral memory testing by means of intracarotid injection of etomidate were analyzed. Results There was a significant difference in memory scores when injections were on the side ipsilateral to the epileptogenic focus compared with when the injections were on the contralateral side (P < 0.01), supposedly reflecting unilateral hippocampal memory function and dysfunction. In addition, the procedural modification resulted in eradication of all major side effects in the ensuing 18 patients. Conclusions The technical modification of the Montreal procedure from continuous to bolus injection effectively enabled the demonstration of the relative weakness of the memory function of the epileptogenic hemisphere. The revised etomidate procedure provided the clinical information on unilateral hippocampal memory function necessary for surgical decision.